2013
DOI: 10.1590/1414-431x20133030
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen sulfide donor, Lawesson's reagent, prevents alendronate-induced gastric damage in rats

Abstract: Our objective was to investigate the protective effect of Lawesson's reagent, an H2S donor, against alendronate (ALD)-induced gastric damage in rats. Rats were pretreated with saline or Lawesson's reagent (3, 9, or 27 µmol/kg, po) once daily for 4 days. After 30 min, gastric damage was induced by ALD (30 mg/kg) administration by gavage. On the last day of treatment, the animals were killed 4 h after ALD administration. Gastric lesions were measured using a computer planimetry program, and gastric corpus pieces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…It has previously been reported that differences in GPx-1 and SOD activities could serve as a marker of the pathological condition [41]. Our present observations support recent findings that H 2 S-releasing Lawesson's reagent or another CO donor, dimanganese decacarbonyl, protected gastric mucosa against alendronate-induced gastric damage via regulation of oxidative stress as manifested by an increase in reduced glutathione content and a decrease in MDA content in rat gastric mucosa injured by alendronate [42,43]. Thus, we conclude that the antioxidative properties of the gaseous mediators CO and H 2 S can contribute, at least in part, to the observed gastroprotective effect of these molecules against aspirininduced gastric damage.…”
Section: Discussionsupporting
confidence: 91%
“…It has previously been reported that differences in GPx-1 and SOD activities could serve as a marker of the pathological condition [41]. Our present observations support recent findings that H 2 S-releasing Lawesson's reagent or another CO donor, dimanganese decacarbonyl, protected gastric mucosa against alendronate-induced gastric damage via regulation of oxidative stress as manifested by an increase in reduced glutathione content and a decrease in MDA content in rat gastric mucosa injured by alendronate [42,43]. Thus, we conclude that the antioxidative properties of the gaseous mediators CO and H 2 S can contribute, at least in part, to the observed gastroprotective effect of these molecules against aspirininduced gastric damage.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic oral administration of ALD also caused hemorrhagic lesions in the mucosa of the glandular stomach, indicating true ulcer formation, and this was also supported by the histopathological findings of edema, increased inflammatory cells, and epithelial cell loss [15,16,26].…”
Section: Discussionmentioning
confidence: 58%
“…In an effort to understand the mechanism through which H 2 S exerts its functions, animals were pretreated with glibenclamide, which binds and inhibits K ATP . It was found that glibenclamide ameliorated the protective effect of Lawesson's reagent, suggesting the involvement of K ATP channels in H 2 S's role in protection against ALD‐induced gastric damage . Even though Lawesson's reagent was found to release H 2 S, which shows pharmacological effects in various studies, there are certain properties that need improvement.…”
Section: Hydrogen Sulfide Prodrugs and Delivery Approachesmentioning
confidence: 99%
“…122 In more recent times, a study was carried out by Medeiros et al to understand the effect of Lawesson's reagent on gastric damage caused by alendronate (ALD)-a biphosphate drug used for osteoporosis and several other bone diseases. 123 ALD is responsible for mucosal damage, which could lead to hemorrhage, infiltration of inflammatory cells, and loss of epithelial cells. Rats were pretreated with saline or Lawesson's reagent (27 μmol/kg) once daily for 4 days.…”
Section: Lawesson's Reagent and Analoguesmentioning
confidence: 99%
See 1 more Smart Citation